Efficacy and safety of transurethral plasmakinetic resection of prostate versus transurethral resection for benign prostatic hyperplasia: a systematic review and meta-analysis - Yong-Bo WANG; Si-Yu YAN; Xing HUANG; Xing-Pei GUO; Yu-Qing DENG; Jia-Ao LOU; Jia-Min GU; Ying-Hui JIN; Xiao-Dong LI; Xian-Tao ZENG (Yixue xinzhi zazhi)
Objective To systematically evaluate the efficacy and safety of transurethral plasmakinetic prostatectomy (TUPKP) and trans urethral resection of prostate (TURP) in the treatment of benign prostatic hyperplasia (BPH).Methods We searched the databases of PubMed, Embase, Web of Science, the Cochrane Library, CNKI, Weipu, China Biomedical Literature Database and Wanfang Database, and collected relevant randomized controlled trials (RCTs) from their inception to September 15, 2020. Data extraction and assessment of risk of bias were performed by two reviewers independently. Meta-analysis was performed using Stata 16.0 software.Results A total of 45 RCTs involving 6 490 subjects were included. The results of Meta-analysis showed that, in patients with normal volume of prostate (